A Framework of Drone-based Learning (Dronagogy) for Higher Education in the Fourth Industrial Revolution - Norman, Helmi; Nordin, Norazah; Amin Embi, Mohamed; Zaini, Hafiz; Ally, Mohamed (International Journal of Engineering and Technology, 2018)
The fourth industrial revolution is impacting the world in three megatrends which include physical, digital, and biological trends. Drone technology is gaining more interest from all sectors including the education sector. Drones is one of the technologies in the physical world that has the potential for redesigning education in the fourth industrial revolution. Yet, as the technology is newly made for the public, itsâ€™ affordances in educational environments are still not fully understood. Hence, the study investigates dronagogy for higher education and develops a framework for dronagogy a learning strategy. The study applies a case study using small autonomous drone integration in using problem-based learning and MOOCs using the pedagogy-space-technology framework. Learning analytics are used for assessment of learning in terms of active learning time while dronagogy was applied as learning tasks. The findings revealed that that dronagogy could be used as a learning strategy in different learning contexts and dronagogy could be used to guide integration of drone-based learning in higher educational settings for the fourth industrial revolution.Â Â